The impacts of loan default on bank performance: A case of Grameen Bank before and during the pandemic - Bintee, Tabassum Alam (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.